Wireless sensor networks Zigbee applied on sewage treatment station - Garcia, A. S.; Tose, T.; Ramalho, L. A. [UNESP]; Sícari, D. D N (Institution of Engineering and Technology (IET), 2012)
The good efficiency in a sewage treatment plant (WWTP) is a great importance to the environment. The management of electromechanical equipment installed in these stations is a major challenge due to the fact that they are installed on areas of difficult access and maintenance unhealthy and making the time for the correction of any faults is extended. This paper proposes the development of a Wireless Sensor Network (WSN), in order to monitor electromechanical equipment, allowing the Concessionaire a predictive control in real time. The design of a wireless sensors network for monitoring equipment requires not only the development and assembly of the sensor modules, but must also include the development of software for managing the data collected. Thus, this work includes a Zigbee WSN, small, adapted for monitoring of electromechanical equipment and environmental conditions of a WWTP, type stabilization pond, installed in an area of approximately 0.15 km 2 and the average flow of 320 liters of treatment per second. The experimental results show that this monitoring system can perform with the collection of parameters of performance and quality assessment at the station.
Keywords: Electromechanical equipment; Monitoring equipments; Sewage treatment plant; Wireless sensor network; ZigBee; Environmental conditions; Monitoring equipment; Monitoring system; Parameters of performance; Predictive control; Quality assessment; Real time; Sensor modules; Wireless sensors networks; Equipment; Sensors; Sewage treatment plants; Zigbee; Wireless sensor networks